Increased signal complexity is associated with increased mating success. (18th May 2022) - Choi, Noori; Adams, Matt; Fowler-Finn, Kasey; Knowlton, Elise; Rosenthal, Malcolm; Rundus, Aaron; Santer, Roger D.; Wilgers, Dustin; Hebets, Eileen A.
Abstract : The evolution of complex signals has often been explored by testing multiple functional hypotheses regarding how independent signal components provide selective benefits to offset the costs of their production. In the present study, we take a different approach by exploring the function of complexity per se . We test the hypothesis that increased vibratory signal complexity—based on both proportional and temporal patterning—provides selective benefits to courting male Schizocosa stridulans wolf spiders. In support of this hypothesis, all of our quantified metrics of vibratory signal complexity predicted the mating success of male S. stridulans. The rate of visual signalling, which is mechanistically tied to vibratory signal production, was also associated with mating success. We additionally found evidence that males can dynamically adjust the complexity of their vibratory signalling. Together, our results suggest that complexity per se may be a target of female choice.